Systematic review and meta-analysis of pain management after tonsillectomy - Katharina Geißler; Daniel Scham; Winfried Meißner; Peter Schlattmann; Orlando Guntinas-Lichius (Scientific Reports)
Abstract Tonsillectomy is one of the most common operations. Tonsillectomy is also one of the most painful surgical procedures. However, there is still no satisfactory standard for postoperative pain management. Four databases (Cochrane Library, Ovid Technologies, PubMed, Web of Science) were searched for the period from 1908 to 2019. The systematic literature review followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Data were pooled using random-effects and fixed-effects models. Randomized controlled trials, reviews and meta-analyses were included. Primary outcomes were quantitative pain intensity in the first 24 h after tonsillectomy and on days 1, 3, and 7 postoperatively. The search yielded 1594 publications, of which 111 publications with 7566 patients, both children and adults, could be included. Intraoperative medication with intravenous dexamethasone significantly reduced pain (mean difference [MD] -0.42; 95% confidence interval [CI]: -0.61- -0.24). Among the local anesthetics, only the preoperative injection of levobupivacaine into the tonsillar compartment was able to provide sufficient pain reduction up to three days after tonsillectomy (MD: -1.92; 95% CI: -2.73 - -1.11). Preoperative or intraoperative administration of non-steroidal anti-inflammatory drugs (NSAIDs) significantly reduced pain (MD: -0.75; 95% CI: -0.87- -0.63). Steroids and NSAIDs are an important part of pain management after tonsillectomy.